APPLICATION OF NATURAL LANGUAGE PROCESSING IN UNDERSTANDING AND ANALYZING FOOD AND NUTRITION-RELATED TEXTS (International Journal of Food and Nutritional Sciences, 2021)
Natural Language Processing (NLP) is increasingly pivotal in the domain of food and nutrition, offering innovative ways to analyze and interpret vast amounts of textual data. This paper explores the application of NLP techniques in understanding and analyzing food and nutrition-related texts, encompassing scientific literature, dietary guidelines, health reports, and social media discussions. The utilization of NLP enables the extraction of valuable insights from unstructured data, which is critical for advancing personalized nutrition, dietary recommendations, and public health strategies. Key NLP techniques applied include Named Entity Recognition (NER) for identifying and classifying food-related entities, sentiment analysis for gauging public opinion on dietary trends, and topic modeling for uncovering underlying themes in nutrition discussions. Additionally, NLP facilitates the development of sophisticated food information retrieval systems, enhancing the accuracy of nutritional information and dietary advice. The integration of machine learning models with NLP further refines the analysis by enabling predictive analytics and trend forecasting. The benefits of NLP in food and nutrition are multi-faceted. It allows for the aggregation and synthesis of diverse data sources, supports evidence-based decision-making, and aids in identifying emerging health trends and dietary patterns. This paper discusses case studies and practical implementations of NLP in nutrition research and health communication, highlighting the challenges and future directions in this evolving field. The potential for NLP to transform food and nutrition research, improve public health outcomes, and support personalized nutrition interventions is significant.